Developing a Comprehensive Regional Resilience Index through Analytic Hierarchy Process: A Five-Dimensional Approach in Bogor Regency, Indonesia - Tjahjo Tri Hartono; Aidha Zulaika; Yuggo Afrianto; Immas Nurhayati; Ratna Pratini; Mas Davino Sayaza (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
This study develops a comprehensive five-dimensional Regional Resilience Index (Indeks Ketahanan Wilayah/IKW) for Bogor Regency, Indonesia, integrating governance capacity and social capital dimensions alongside traditional human development, food security, and disaster risk indicators. Stakeholder-derived weights through the Analytic Hierarchy Process (n=25 experts) yielded the following priority ranking: Human Development (0.28), Disaster Risk (0.24), Food Security (0.22), Governance Capacity (0.15), and Social Capital (0.11), with consistency ratio CR=0.073. Spatial analysis across 40 subdistricts revealed significant heterogeneity (CV=18.7%), with k-means clustering identifying three distinct resilience typologies: High (8 subdistricts, IKW>65), Moderate (24 subdistricts, IKW 51-65), and Low (8 subdistricts, IKW<51). Comprehensive validation achieved: Cronbach's alpha 0.78, MAPE 1.12%, cross-validation RMSE 2.87, Monte Carlo 90% confidence interval of +/-3.2 points, and significant outcome correlation with post-flood recovery times (r=-0.67, p<0.01). Baseline IKW 2025: 58.42 (Moderate). Multi-scenario projections to 2030: baseline 63.15, optimistic 68.24 (High category transition), pessimistic 55.78. The framework provides actionable guidance for evidence-based regional development planning.